Modeling and Forecasting the Development of Precancerous Diseases of the Oral Mucosa Based on Medical and Social Risk Factors - Kolenko, Ю. Г.; Nesin, О. Ф.; Fedianovich, І. М. (Actual Dentistry, 2026)
Relevance. According to WHO data, about half of oral cancer cases are caused by factors that can be influenced to reduce the number of patients. Carcinogenic factors in the environment and lifestyle are considered to be the cause of 90–95% of all malignant neoplasms. The study aims to analyze the significance of medical, social, and clinical characteristics of patients with precancerous diseases in relation to their impact on disease progression. Materials and methods. The prevalence and structure of precancerous diseases of the oral cavity among a statistically significant sample of the Kyiv population were studied by recording the corresponding diagnoses of patients who visited the Dental Centre at the Department of Therapeutic Dentistry of the Bogomolets National Medical University in 2020–2025. The study involved 423 patients aged 20 to 87 years. The research program included the analysis of patient complaints and medical history data, clinical examination, and the use of additional diagnostic methods. Statistical processing of the obtained data was performed using the STATISTICA program. Research results. The structure and prevalence of precancerous SOPR diseases detected based on the results of a comprehensive examination of 423 patients were as follows: erosive and hyperkeratotic (typical) forms of lichen planus—in 187 (44.21%), flat form of leukoplakia—in 105 (24.82%), erosive and verrucous forms of leukoplakia—in 70 (16.55%), chronic mucosal ulcers—in 18 (4.26%), Manganotti’s cheilitis—in 15 (3.55%), meteorological and actinic cheilitis—in 15 (3.55%), post-radiation cheilitis and stomatitis—in seven (1.64%), and papilloma—in six (1.42%) patients. Twenty (4.51%) patients were diagnosed with SOPR cancer. To predict the development of oncological diseases in patients, models were constructed that account for the relationship between the probability of developing precancerous diseases and risk factors. Conclusion. The study identified medical, social, and clinical risk factors for the development of precancerous diseases in the Ukrainian population, based on which criteria were established to define high-risk groups for this pathology.